Association between community-acquired pneumonia and platelet indices: A case-control study - Hajar Motamed; Homayoon Bashiri; Farideh Yari; Arezo Bozorgomid; Mosayeb Rostamian; Yosef Azarakhsh; Azam Hosseini; Roya Chegene Lorestani (Journal of Acute Disease, 2021)
Objective: To examine whether the platelet index would be applicable for the diagnosis of community-acquired pneumonia (CAP). Methods: In this study, 64 CAP patients (the case group) and 68 healthy children (the control group) were included from 2017 to 2018. Baseline variables were recorded including total white blood cells, neutrophils, lymphocytes, red blood cells, platelet, mean platelet volume, platelet distribution width, erythrocyte sedimentation rate, and C-reactive protein, and compared between the case group and the control group. The cutoff value, sensitivity, and specificity of neutrophil-to-lymphocyte ratio, platelet, neutrophils, lymphocytes, and platelet larger cell ratio were calculated by receiver-operating characteristic curves. Results: The median platelet count of the case group and the control group were (411.09±67.40) mm3 and (334.48±78.15) mm3, respectively (P=0.000). The median neutrophil count of the case group was higher than that of the control group (P=0.000), while the lymphocyte level of the case group was lower (P=0.000). Differences in other variables including the mean platelet volume, platelet distribution width, C-reactive protein, and erythrocyte sedimentation rate were not statistically significant between the two groups. Conclusions: Due to the different levels of platelet, neutrophil and lymphocyte indices in the case and the control group, these indices can be used simultaneously for the diagnosis of CAP.